Cultural Capital and Learning Strategies: A Bourdieuian Perspective on Elementary Education - Muhammad Amin; Raharjo Raharjo; Shodiq Abdullah; Ahmad Fuad Hasyim Hafid Suyuthi (Al Ibtida: Jurnal Pendidikan Guru MI, 2025)
Abstract This study aims to explore the relationship between cultural capital and teaching strategies in the context of primary education, employing a Bourdieuian perspective. The focus of this research is on teachers at Madrasah Ibtidaiyah Negeri in Magelang Regency. A qualitative method was utilized, with data collected through in-depth interviews and classroom observations. The findings reveal that teachers’ cultural capital, including their knowledge, values, and experiences, significantly influences their choice and implementation of teaching strategies in the classroom. Teachers with a rich cultural capital tend to adopt more innovative and adaptive strategies, which enhance student engagement in the learning process. Furthermore, the study identifies challenges faced by teachers in integrating cultural capital into their teaching practices. These findings provide helpful guidance in the development of educational policies and teacher training programs, ultimately improving the quality of education in Madrasah Ibtidaiyah.Keywords: cultural capital, teaching strategies, Bourdieuian perspective, Madrasah Ibtidaiyah. AbstrakPenelitian ini bertujuan untuk mengeksplorasi hubungan antara modal budaya dan strategi pembelajaran dalam konteks pendidikan dasar, dengan pendekatan perspektif Bourdieu. Fokus penelitian ini adalah pada guru-guru di Madrasah Ibtidaiyah Negeri di Kabupaten Magelang. Metode penelitian yang digunakan adalah kualitatif dengan teknik pengumpulan data melalui wawancara mendalam dan observasi. Hasil penelitian menunjukkan bahwa modal budaya yang dimiliki oleh guru, seperti pengetahuan, nilai-nilai, dan pengalaman, berdampak dalam menentukan pilihan dan penerapan strategi pembelajaran di kelas. Guru yang memiliki modal budaya yang kaya cenderung menggunakan strategi yang lebih inovatif dan adaptif, yang dapat meningkatkan keterlibatan siswa dalam proses pembelajaran. Selain itu, penelitian ini juga mengidentifikasi tantangan yang dihadapi oleh guru dalam mengintegrasikan modal budaya ke dalam praktik pembelajaran. Temuan ini dapat memberikan wawasan bagi pengembangan kebijakan pendidikan dan pelatihan guru, serta meningkatkan kualitas pembelajaran di Madrasah Ibtidaiyah.Kata kunci: modal budaya, strategi pembelajaran, Bourdieuian perspective, Madrasah Ibtidaiyah.